Genotyping of Staphylococcus aureus Isolates Based on Methicillin-Resistance Genes and its Relatedness to some Putative Virulence Factors - Kandala, Nuha. J.; Abdulateef , Mahammad; Imad, Nadia; Imad, Nadia (Iraqi Journal of Science, 2022)
The emergence and spread of methicillin-resistant Staphylococcus aureus (MRSA) was a public health problem worldwide that causes nosocomial and community infections. Forty three isolates (71.66%) were characterized as S.aureus, were isolated from 60 different clinical specimens (blood, nose, wound, urine and vaginal) collected from patients from different hospitals of Baghdad. All isolates were resistant (100%) to Aztreonam, Carbenicillin, Cifixime, Cefoxitin, Ceftazidime, and showed high resistance to each of Methicillin, Oxacillin, Ampicillin and Penicillin . the MRSA isolates were typed based on (SCCmec) typing ,the result revealed that SCCmecIVa was the most common in isolates (41.86%), following type IVc (20.93%), type II(16.27%). Virulence factors were identified to detect genes encoding for Hlg,Pvl,ClfA,Tsst-1 and Eta, and the result showed the most prevalent gene was hlg (65.11%), following pvl (53.48%), clfA (51.16%), tsst-1(18.60%),eta (11.62%). The virulence genes profiles were observed, and the most frequent was clfA-hlg-pvl (23.25%), clfA-hlg-pvl-tsst-1 (6.97%),clfA-hlg-tsst-1(4.65%).Analysis of genetic similarity relationship, showed the isolates of S.aureus were classified into two main clusters . This result indicates that there a diversity in virulence genes profiles among MRSA isolates according to SCCmec types, and SCCmec IVa carried hlg, pvl , clfA genes was the most prevalent in Baghdad hospital isolates .